Penerapan Sistem Informasi Geografi pada Traffic Management Center - Ricky, Michael Yoseph (Bina Nusantara University, 2011)
This study aims to analyze and design a geographic information system as a tool for traffic flow monitoring and regulation for the Traffic Management Center Polda Metro Jaya. Data was collected through field studies relating to the engineering of software and hardware. Interviews were also conducted to the relevant parties. Then it is proceeded with systems analysis and design methods. This system succeeded in helping the Traffic Management Center to find out the points which are prone to cause congestion, so that it can quickly obtain the traffic flow information.